ORGANIZATIONAL PERFORMANCE OF PUBLIC SERVICES AT THE GENERAL ELECTION COMMISSION (KPU) OF GORONTALO CITY - Idham Mantali; Rauf A. Hatu, Yanti Aneta, Dian Ekawaty Ismail (Adisam Publisher, 2025)
This study aims to analyze the quality of public services provided by the General Election Commission (KPU) of Gorontalo City. Data were collected through interviews, observations, and documentation, and then analyzed using qualitative analysis methods. The findings reveal that the quality of services offered by KPU Gorontalo City staff is optimal. Facilities and infrastructure, such as parking spaces, waiting rooms, internet connectivity, and other supporting amenities, provide significant comfort for service users and are updated to meet modern needs. Services are delivered promptly according to standard operating procedures (SOP) and are provided free of charge without any additional fees. This favorable condition is reinforced by the office environment, which prominently displays posters or notice boards emphasizing a zero-tolerance policy for illegal levies. However, the quality of services can be further improved by enhancing staff reliability in IT. This could be achieved through training existing staff or recruiting skilled IT personnel. Such improvements would support the technology-driven activities and performance of the KPU Gorontalo City.